Hydrogen sulfide inhibits IL-8 expression in human keratinocytes via MAP kinase signaling - Mirandola, P.; Gobbi, G.; Micheloni, C.; Vaccarezza, Mauro; Di Marcantonio, D.; Ruscitti, F.; De Panfilis, G.; Vitale, M. (2011)
Sulfur is able to penetrate the skin, and a sulfur-rich balneotherapy has been suggested to be effective in the treatment of psoriasis. Psoriasis is now considered a genetically programmed, immune-mediated, inflammatory disease, in which intralesional T lymphocytes trigger keratinocytes to proliferate and perpetuate the disease process. Interleukin (IL)-17 and IL-22 produced by Th1/Th17 lymphocytes induce IL-8 secretion by keratinocytes, a key event in the pathogenesis of the disease. It is now clear that mitogen-activated protein kinase (MAPK) (extracellular signal-regulated kinases (ERK) 1 and 2) activity is required for IL-17-induced IL-8 synthesis by keratinocytes, and, in fact, MAPK activity is increased in lesional psoriatic skin. Here, we demonstrate both in vitro and in vivo on primary psoriatic lesions that pharmacological inhibitors of ERKs as well as hydrogen sulfide not only reduce the basal expression and secretion of IL-8, but also interfere with IL-17- and IL-22-induced IL-8 production. These observations, together with the known anti-inflammatory activity of H2S, are relevant to understanding some previously unexplained biological effects exerted by sulfur therapy.